Relationship Between Type 2 Diabetes and White Matter Hyperintensity: A Systematic Review - Wang, Dan-Qiong; Wang, Lei; Wei, Miao-Miao; Xia, Xiao-Shuang; Tian, Xiao-Lin; Cui, Xiao-Hong; Li, Xin (Frontiers in Endocrinology, 2020)
White matter (WM) disease is recognized as an important cause of cognitive decline and dementia. White matter lesions (WMLs) appear as white matter hyperintensities (WMH) on T2-weighted magnetic resonance imaging (MRI) scans of the brain. Previous studies have shown that type 2 diabetes (T2DM) is associated with WMH. In this review, we reviewed the literature on the relationship between T2DM and WMH in PubMed and Cochrane over the past five years and explored the possible links among the presence of T2DM, the course or complications of diabetes, and WMH. We found that: (1) From a macroscopic point of view, the relationship between T2DM and WMH remains controversial; (2) From the microscopic point of view, most studies observed a decrease in the integrity of WM in T2DM or prediabetes, especially in the FA values, mainly concentrated in the corpus callosum, combined tract, and other parts, and found that DKI detected more changes in WM microstructures than diffusion tensor imaging (DTI) did; (3) From the relationship between brain structural changes and cognition in T2DM, the poor performance in memory, attention, and executive function tests associated with abnormal brain structure is consistent; (4) Diabetic microangiopathy or peripheral neuropathy may be associated with WMH, suggesting that the brain may be a target organ for T2DM microangiopathy; (5) Laboratory markers such as insulin resistance and fasting insulin levels were significantly associated with WMH, but the correlation between the duration of T2DM and HbA1c value and WMH was not clear.